THE FOOD AS A HUMAN RIGHT AND RISK IN A COMPLEX SOCIETY - Alzira Zuin, Aparecida Luzia (Revista Inclusiones, 2021)
This work aims to analyze the theme of food as a human right and risk in a complex society from the angle of the Study of Risk an Ecology of the Human Rights . Here, risk condensates a particular symbiosis of future and society, allows the construct of communication and describes the chance of reflecting about the future. It is based on two questions: the semantic load underlying the terms security, insecurity and risk; and how the food insecurity modality is present in contemporary society. The idea is that civilization has advanced trying to abolish the imminent perils of catastrophes, but it did not find sustainability or a favorable balance to eliminate the complex social problems it produces. Thus, from the very decision structures risk is fomented. It concludes on the paradoxical aspect of this society, whose events operate on risk productions: the more food production, more food insecurity the more communication and education, more disinformation; the more knowledge, more un- knowledge.